Pancreatic Cystic Lesions on MRI: What Is The Likelihood of a Present or Future Diagnosis of Pancreatic Carcinoma?. Issue 5 (24th September 2022) - Alwahbi, Omar; Larocque, Natasha; Kulkarni, Ameya; Gopee‐Ramanan, Prasaanthan (Prasa); Ghumman, Zonia; Sarkar, Rahul; Kagoma, Yoan K.; Alabousi, Abdullah; Tsai, Scott; Wat, Josephine; McInnes, Matthew; van der Pol, Christian B.
Abstract : Background: Pancreatic cystic lesions (PCLs) are followed for years due to older and likely biased works demonstrating a strong association with pancreatic carcinoma; more recent data are needed clarifying this relationship. Purpose: To determine the association between PCLs on MRI and a synchronous or future diagnosis of pancreatic carcinoma. Study type: Single‐center retrospective cohort. Population: A total of 192 patients (111 female, 58%) with median age 66 years (range 26–87 years) with PCLs on abdominal MRI from 2011 to 2016. Field Strength/Sequences: 1.5 T and 3 T, including T2 WI, T1 WI, diffusion weighted imaging and contrast‐enhanced T1 WI. Assessment: Each PCL was reviewed independently by 2 of 10 fellowship‐trained abdominal radiologists. Fukuoka guideline worrisome features and high‐risk stigmata were evaluated. Follow‐up imaging and clinical notes were reviewed within a system that captures pancreatic carcinoma for the region, for a median follow‐up of 67 months (interquartile range: 43–88 months). Statistical Tests: Pancreatic carcinoma prevalence and incidence rate for future carcinoma with 95% confidence intervals (95% CI). Fisher exact test, logistic regression with odds ratios (OR) and the Wilcoxon rank‐sum test were used to assess PCL morphologic features with the Kolmogorov–Smirnov test used to assess for normality. P < 0.05 defined statistical significance. Results: The prevalence of pancreatic carcinoma on initial MRI showing a PCL was 2.4% (95% CI: 0.9%, 5.2%). Thickened/enhancing cyst wall was associated with pancreatic carcinoma, OR 52 (95% CI: 4.5, 1203). Of 189 patients with a PCL but without pancreatic carcinoma at the time of initial MRI, one developed high‐grade dysplasia and none developed invasive carcinoma for an incidence rate of 0.97 (95% CI: 0.02, 5.43) and 0 (95% CI: 0, 3.59) cases per 1000 person‐years, respectively. Data Conclusion: A low percentage of patients with a PCL on MRI had a pancreatic carcinoma at the time of initial evaluation and none developed carcinoma over a median 67 months of follow‐up. Evidence Level: 3 Technical Efficacy: 5